2014
DOI: 10.1517/14728222.2014.941808
|View full text |Cite
|
Sign up to set email alerts
|

TargetingCDKN3in cervical cancer

Abstract: CDKN3 might be useful not only as marker for survival and selection of CC patients for additional chemotherapy or specific target cancer therapy, but also as a potential target to develop specific small drugs to combat CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…CDK6 expression was downregulated in MAFB knockdown SW1116 cells, while CDKN3, CUL1 and CUL3 were upregulated (Figure 3A). This was consistent with the findings of other G1 phase arrest studies [2124]. We also found that CCNB1 and CCND1 were downregulated (Supplementary Figure S3), which was in agreement with previous work [15].…”
Section: Resultssupporting
confidence: 94%
“…CDK6 expression was downregulated in MAFB knockdown SW1116 cells, while CDKN3, CUL1 and CUL3 were upregulated (Figure 3A). This was consistent with the findings of other G1 phase arrest studies [2124]. We also found that CCNB1 and CCND1 were downregulated (Supplementary Figure S3), which was in agreement with previous work [15].…”
Section: Resultssupporting
confidence: 94%
“…The association between CDKN3 and tumorigenesis has previously been reported in several studies ( 4 6 ). However, the molecular mechanisms underlying the effects of CDKN3 on cell cycle arrest, apoptosis and cell migration remain to be determined.…”
Section: Introductionmentioning
confidence: 52%
“…It was initially identified as a CDK inhibitor, which interacts with, and dephosphorylates CDK2, thus preventing its activation ( 4 ). Aberrant expression of CDKN3, including deletion, mutation, or overexpression has been reported in numerous types of cancer ( 4 6 ). However, the exact role of CDKN3 in the progression of breast cancer remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our data, upregulation of CDKN3 gene, together with other genes, has been associated with decreased survival of patients with lung cancer [ 40 ] and astrocytoma [ 43 ]. Furthermore, CDKN3 inhibition in many cell lines decreases cell proliferation, suggesting that this gene acts as an oncogene [ 47 ]. However, overexpression of CDKN3 has been associated with the inhibition of cell proliferation in glioblastoma [ 42 , 48 ] and leukemic [ 49 ] cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CDKN3 protein, a dual-specificity protein phosphatase of the Cdc14 phosphatase group, also appears to be essential in the regulation of mitosis exit. It interacts with CDK1 (CDC2) and inhibits its activity, and dephosphorylates many of the proteins phosphorylated by CDK1 [ 47 , 48 ]. CDKN3 and other Cdc14 phosphatases appear to be essential for antagonizing Cdk activity in late mitosis, allowing cells to exit mitosis and enter cytokinesis.…”
Section: Discussionmentioning
confidence: 99%